Penguatan Etika Administrasi Untuk Kualitas Pelayanan Kepegawaian Di Palangkaraya, Kalimantan Tengah - Joe Audinno Yon Saputra; Julian Griseldio Bungai; Papel Ray Yoga Simamora (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study seeks to examine policies that promote ethical administration and how these policies affect improvements in staff services in Palangkaraya. The methodology used is qualitative, employing a policy analysis approach, and data was collected solely from online sources, including official documents from the Palangkaraya City Government, such as Regional Regulations, Mayor Regulations, and other relevant strategic documents. This study found that the strengthening of ethics in personnel administration in Palangkaraya is regulated by three main policy groups: normative policies, namely the Code of Ethics and Regulations on Civil Servant Discipline; procedural policies, namely the Mayor's Regulation on Personnel Service SOPs, which outlines ethical service standards; and development policies, which are included in regional development plans. According to the analysis, this framework has essentially incorporated contemporary ethical administration principles, such as accountability, transparency, and fairness. However, its implementation still requires improvement in terms of a comprehensive monitoring system and continuous evaluation. In conclusion, the Palangkaraya City Government has a solid policy foundation for strengthening administrative ethics, the effectiveness of which depends on successful implementation, synergy between policies, and consistency in enforcing regulations to improve the quality of civil service. The recommendations proposed include the need for continuous education and the establishment of an integrated monitoring and evaluation system to ensure the internalization of ethical principles in daily civil service procedures.